ANALISIS PENERJEMAHAN GAYA BAHASA METAFORA DALAM NOVEL L’ASSOMMOIR KARYA ÉMILE ZOLA - Aditya, Rhizki Tama (Universitas Hasanuddin, 2023)
This research has two objectives, are identifying the metaphors in the novel